PENGHARAMAN KHAMR DALAM BINGKAI TAFSIR NUZULI: KAJIAN PENAFSIRAN IZZAH DARWAZAH DAN AL-JABIRI - Affandi, Abdullah (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2021)
Khamr or more synonymous with intoxicating drinks has been known by Muslims as a drink that is forbidden to consume. When viewed from the perspective of the history of the formation of Islamic law, basically the labeling of haram law on khamr is not all at once. There are at least 4 stages that are passed until the formation of the haram label. Allah forbids khamr or other intoxicating things in a gradual way (not succinctly or immediately forbidden). This article will discuss the regulation of the prohibition of alcohol based on the chronological interpretation represented by Izzah Darwazah and Abid al-Jabiri. Keywords: khamr, tafsir nuzuli